The Effectiveness of Integrating Jayapura’s Local Wisdom to Students' Science Process Skills and Conceptual Understanding of Physics - Risamasu, Putu Victoria M.; Pieter, Jan (Department of Physics Education, Universitas Mataram, 2024)
Students who live in dominant customs and culture in their daily lives sometimes experience obstacles when studying physics at school. This research aims to integrate local wisdom and local potential that exist in the Jayapura community in physics lessons and see its impact on students' science process skills and conceptual mastery. The research method used in this research is quantitative with a Quasi-Experimental research type with a Non-equivalent Control Group Design. Data collection techniques used test instruments and learning observations. The instrument used in data collection was test. Data analysis used N-gain analysis and Manova test using SPSS program. The subjects in this research were class XI students from three public high schools in Jayapura City who were selected using purposive sampling technique. The research results showed that the integration of local wisdom and local potential of the Jayapura Community had a positive impact on the experimental class and there was a significant increase in N-gain. Furthermore, the Manova test results showed that there were differences in science process skills and concept mastery between the experimental class and the control class. Furthermore, educators can develop E-LKPD based on the local wisdom of the Jayapura community to accommodate the use of technology in learning and preserve the local culture of the community.